ASSESSMENT OF COGNITIVE STATUS IN CEREBRAL DISORDERS IN PATIENTS WITH DIABETES MELLITUS - Otabek B. Nadjmitdinov; Akramjon A. Sobirov; Ilxomjon A. Jalolov (Central Asian Journal of Medicine, 2025)
Diabetes mellitus is one of the most significant risk factors for the development of cerebrovascular disorders, which can lead to a decrease in cognitive functions. This study examines the relationship between diabetes mellitus and cognitive impairment due to cerebral changes.